Minor Ailment Service in Costa Rica: criteria to dispense a medicine or to refer to the physician - Pereira Céspedes, Alfonso (2021)
Introduction: Minor Ailment Service is a very common pharmaceutical service. The objective was to evaluate the criteria associated with the referral to physician or with dispensing medicines in those consultations in Costa Rica. Method: Observational descriptive cross-sectional multicenter exploratory study of: Minor Ailment Service consultations in 30 community pharmacies, and analyzed the factors associated with to refer to the physician or dispense medicines. Results: There were 1,538 consultations, of which medicines are dispensed in 92.3% of them (n=1,420), referred to the physician in 6.7% (n=103). In relation to the intervention of referring to the physician, the bivariate analysis showed a statistically significant association with them, highlighting the criteria suspected adverse drug reaction, medicines use currently for other health problem and duration of the health problem ≥7 days. Conclusions: The service is complex and shows that the pharmacist follows a series of criteria to make a decision –the referral to physician or dispensing medicines–. There are seven important criteria according to this study. However, the one that stands out is suspected adverse drug reaction, followed by medicines use currently for other health problems, duration of the health problem ≥7 days and pregnancy/lactation.